A virus disaster recovery plan framework for academic computing center - Gurhan, Mohamed Ismail (2014)
This thesis presents a Virus disaster recovery plan framework for academic computing centre. The CICT-UTM is taken as case study. The proposed framework consists of seven phases of disaster recovery plan which has been enhanced in improved by researcher based on past studies. The phases of the framework are risk assessment, prevention, preparedness, reaction, immediate recovery, restoration and review. The type of disaster in this study focuses on virus threats. In addition, the framework describes the virus management process in each phases which is before, during and after virus occurs. The framework of virus disaster recovery plan outlined here should provide the dictionary necessary for planning any Academic Computing Centre. The project is a case study based with interviews, documentation and questionnaire as the key to improve virus disaster recovery plan and any similar organization to provide a knowledge feedback. An enhanced framework will be proposed that will be validated by an expert.